Penerapan Model Pembelajaran Inkuiri Terbimbing untuk Meningkatkan Hasil Belajar Kognitif Siswa Kelas X IPA di SMA Negeri 2 Kendari pada materi ikatan kimia - Nur Azizah; Fahyuddin; Saefuddin (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2023)
This study aims to find out the description of the cognitive learning outcomes of class X IPA students at SMA Negeri 2 Kendari on chemical bonding material using the guided inquiry learning model and conventional learning and to test the differences in students' cognitive learning outcomes between groups of students using the inquiry learning model guided by conventional learning. This research is a quasi-experimental research with a pretest-posttest control group design. The sample in this study was class X IPA 6 as the experimental class and class X IPA 7 as the control class. The data collection technique was carried out by giving the form of 20 multiple choice questions to determine students' initial abilities and giving a final test (posttest) to determine student learning outcomes. Based on the results of the descriptive analysis, the average value of the cognitive learning outcomes of the experimental class students was 82.77, which was higher than the control class, which was 70.97. This can also be seen from the average n-gain value, the n-gain value for the experimental class is 0.7 (high category) while the control class is 0.6 (medium category). Can be it is said that there is a difference in improving students' cognitive learning outcomes between classes taught by guided inquiry learning models and conventional learning.